Neuronal ensemble-specific DNA methylation strengthens engram stability - Gülmez Karaca, Kübra; Kupke, Janina; Brito, David V. C.; Zeuch, Benjamin; Thome, Christian; Weichenhan, Dieter; Lutsik, Pavlo; Plass, Christoph; Oliveira, Ana (Nature Communications, 2020)
Memories are encoded within neuronal ensembles activated during learning. Here the authors show that DNA methylation within neuronal ensembles contributes to the stability of the memory trace, and increases the likelihood of neuronal ensemble reactivation during retrieval.
Gesehen am 30.03.2020